Selection of early maturing maize inbred lines for hybrid production using multiple traits under Strigainfested and Strigafree environments - Badu-Apraku, Baffour; Akinwale, R.O.; Fakorede, M.A.B. (2010)
Striga hermonthica (Del.) Benth.is a majorbiotic constraint to increased maize (Zea mays L.) productionand productivity in West and Central Africa (WCA).Twenty-three early maize inbreds were evaluated underartificial Striga infestation and Striga-free conditions at 2locations for 2 years in Nigeria to identify the most appropriatetraits for selecting Striga resistant inbreds, and identifycandidate parents for hybrid production and introgressionof resistant genes into maize populations. GGEbiplot analysis was used to facilitate selection of inbredson the basis of multiple traits, including Striga-resistance,yield and several other agronomic traits. The results of thegenotype-by-trait (GT) biplot analysis revealed TZEI 3 asthe best inbred for use as source of Striga resistancegenes for introgression into white–endosperm breedingpopulations. Similarly, inbreds TZEI 3, TZEI 2, TZEI 11,and TZEI 15 were identified as potential inbred parentsfor the production of Striga-resistant hybrids based onboth GT biplot and multi-trait selection tools. Striga damagerating at 8 and 10 WAP, ear aspect and ears per plantwere the best traits for indirect selection for yield underinfested conditions while plant height, ear height, ear andplant aspects were the best under non-infested conditions.